Heterogeneity in Bleeding Tendency and Arthropathy Development in Individuals with Hemophilia - Rehill, Aisling M.; McCluskey, Seán; O'Donnell, James S.; Dockal, Michael; Preston, Roger J.S.; on behalf of the iPATH Study Group (Seminars in Thrombosis and Hemostasis, 2021)
People with hemophilia (PWH) have an increased tendency to bleed, often into their joints, causing debilitating joint disease if left untreated. To reduce the incidence of bleeding events, PWH receive prophylactic replacement therapy with recombinant factor VIII (FVIII) or FIX. Bleeding events in PWH are typically proportional to their plasma FVIII or IX levels; however, in many PWH, bleeding tendency and the likelihood of developing arthropathy often varies independently of endogenous factor levels. Consequently, many PWH suffer repeated bleeding events before correct dosing of replacement factor can be established. Diagnostic approaches to define an individual's bleeding tendency remain limited. Multiple modulators of bleeding phenotype in PWH have been proposed, including the type of disease-causing variant, age of onset of bleeding episodes, plasma modifiers of blood coagulation or clot fibrinolysis pathway activity, interindividual differences in platelet reactivity, and endothelial anticoagulant activity. In this review, we summarize current knowledge of established factors modulating bleeding tendency and discuss emerging concepts of additional biological elements that may contribute to variable bleeding tendency in PWH. Finally, we consider how variance in responses to new gene therapies may also necessitate consideration of patient-specific tailoring of treatment. Cumulatively, these studies highlight the need to reconsider the current “one size fits all” approach to treatment regimens for PWH and consider therapies guided by the bleeding phenotype of each individual PWH at the onset of therapy. Further characterization of the biological bases of bleeding heterogeneity in PWH, combined with the development of novel diagnostic assays to identify those factors that modulate bleeding risk in PWH, will be required to meet these aspirations.
Keywords: hemophilia; bleeding heterogeneity; coagulation; fibrinolysis; gene therapy